MALAT1 regulates mRNA processing through sequence dependent RNA–RNA and RNA–protein interactions - Balaji, Adarsh; Hall, Simone; Johnson, Raul; Zhu, Jonathan; Ellis, Lauren; McHugh, Colleen A (Nucleic acids research, 2025)
Messenger RNAs (mRNAs) are subject to multiple layers of gene expression regulation, enabling the production of a large diversity of RNA transcripts and encoded proteins from a smaller number of genes in the human genome. We find that the metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) non-coding RNA regulates mRNA processing through direct RNA–RNA and RNA–protein interactions. MALAT1 interacts with both the TAR DNA binding protein (TDP-43) and the spermine/spermidine acetyltransferase SAT1 pre-mRNA to enhance alternative splicing of SAT1 through direct, sequence-specific interactions. MALAT1 interaction with TDP-43 and SAT1 increases TDP-43 binding affinity for SAT1 pre-mRNA by coordinating tripartite RNA–RNA–protein interactions. These tripartite interactions enhance SAT1 alternative splicing. This mechanism of pre-mRNA processing may not be limited to MALAT1, TDP-43, and SAT1. Similarly, alternative splicing of the liprin-α3 PPFIA3 pre-mRNA at exon 16 by the cleavage stimulation factor subunit 2 protein is enhanced by sequence-specific interactions with MALAT1 RNA. We conclude that the abundant MALAT1 non-coding RNA contains modular RNA–RNA and RNA–protein binding regions that facilitate the processing of mRNA transcripts relevant for neuronal function.